THE ANALYSIS OF ITEM DIFFICULTY AND DISCRIMINATION OF ENGLISH SUMMATIVE TEACHER MADE TEST (TMT) AT MAS MADANI PAO-PAO GOWA - Nawir, Muhammad Syahruddin; Nur, Serliah; Abubakar, Multazam; Asmawati, Andi; Maemunah, (English Language, Linguistics, and Culture International Journal, 2023)
This research was aimed to find out the item difficulty and item discrimination power of English summative test for the second grade students at MAS Madani Pao-Pao Gowa. The researcher used descriptive quantitative method to desribe the item difficulty and discrimination of the items of English summative test. English summative final test used to test students registered as second-grade students at MAS Madani Pao-Pao Gowa in the academic years 2022-2023 was the subject of this study. The instruments documents in the form of test with 25 multiple-choice questions, student's answers, and an answer key. The result of this research, item difficulty is the easy category, there are 2 difficult items, 7 medium items, and 16 easy items. Meanwhile, item discrimination is the poor category, there are 0 excellent items, 0 good items, 0 sufficient items, 10 insufficient items, 15 poor items. Item difficulty and item discrimination are not equal so that it needs to be considered by the teacher when making questions. The items arranged are in accordance with the assessment for students' understanding and abilities. This research to hopes could be highly beneficial to other academics as a reference for future research on similar topics, and may support teachers in their efforts to design and maintain a good test that measures students' true abilities.